Down syndrome in mochica ceramics - Paico-Vílchez, Emiliano (2022)
The Mochica culture developed between 100 B.C. to 750 A.D. In this article, the authors present and describe two ceramics of the Mochica culture in which theyhave identified an adolescent with facies typical of Down syndrome.